Elusive Reaction Intermediates in Solution Explored by ESI‐MS: Reverse Periscope for Mechanistic Investigations. Issue 9 (22nd January 2016) - Iacobucci, Claudio; Reale, Samantha; De Angelis, Francesco
Abstract: Just as periscopes allow a submarine to visually search for objects above the surface of the sea, in a reversed periscope fashion electrospray mass spectrometry (ESI‐MS) can analyze the compounds at the gas phase/liquid phase interface for chemical entities which may exist in solution. The challenge is the identification and structural characterization of key elusive reaction intermediates in chemical transformations, intermediates which are able to explain how chemical processes occur. This Minireview summarizes recent selected publications on the use of ESI‐MS techniques for studying solution intermediates of homogeneous chemical reactions. Abstract : Periscope depth : Electrospray mass spectrometry (ESI‐MS) is a powerful tool for studying reaction mechanisms. The reverse‐periscope concept is proposed to exemplify the potential of ESI‐MS to analyze the gas/liquid interface and identify reaction intermediates present in solution. Mechanisms of complex reactions, such as multicomponent reactions, organocatalyzed reactions, and homogeneous metal catalysis, can be studied in detail.